Learning Self-regulated L2 Writing Under a Cognitive Model - Manashi Gogoi Dutta; Uthaivan Danvivath (My University, 2021)
Abstract This research study has been conducted to experiment an innovative teaching approach believing that when less use of self-regulated learning strategy leads to lower metacognitive learning attitude which results in low proficiency. This study has investigated the consequences of instructionally aroused cognitive involvement load for self-monitoring and self-assessment through facilitation of metacognitive learning strategy use for improving L2 writing skills of Thai undergraduate students. This innovative instructional model for teaching self-regulated L2 writing has been named as Strategic Self-Regulated Metacognitive Activities or S 2 RMCA. The approach of this model has been developed to promote self-regulated learning management. For stimulating the use of learning strategies, a set of self-monitoring and self-evaluating assessment rubric named Strategy Inventories for Learning L2 Writing (SILL2W) has also been devised. A set of questionnaire, pre-post-tests, checklist, and interviews were employed for collecting and analyzing the data. Results of data analyses have shown effectiveness and feasibility of the S 2 RMCA model for teaching self-regulated L2 writing. Satisfactory results have also been shown by participants in their L2 writing skills. So far, research studies conducted on cognitive involvement load, a continuing challenge has always been there regarding the accurate measurement of load via self-reporting and this study has also faced that challenge.
Keywords: Rubric; Self-Regulated Learning; Cognitive Load; Self-assessment; Educational Psychology; Innovative Teaching and Learning Methods